A potential preventive method for scar stenosis after esophageal endoscopic mucosal resection using human amniotic epithelial cells in a porcine model. Issue 1 (9th March 2022) - Konno, Yuji; Sato, Chiaki; Tokodai, Kazuaki; Saito, Masatoshi; Hoshiai, Tetsuro; Taniyama, Yusuke; Okamoto, Hiroshi; Fukutomi, Toshiaki; Ozawa, Yohei; Ujiie, Naoto; Koseki, Ken; Ando, Ryohei; et al.
Abstract: Objectives: The current methods employed for esophageal endoscopic mucosal resection (EMR) involve the risk of adverse postprocedural complications. Therefore, this study aimed to develop a new method to prevent stenosis following a resection procedure using human amniotic epithelial cells in a porcine model. Methods: With the consent of a woman who underwent a cesarean section, amniotic epithelial cells were isolated from the amniotic membrane of the delivered placenta. Six swine were used for this study. Under general anesthesia, four EMRs using cap‐fitted microscope ulcers were performed on each porcine esophagus. Of the four ulcers, the two on the oral side were treated by injecting human amniotic epithelial (AE group) cells, and the remaining two on the anal side were left untreated (control group). One week after the procedure, the swine were sacrificed, and the ulcers were evaluated. The epithelialization rate was calculated by dividing the length of the epithelialized portion of each section by the length of the ulcer, which was determined using an optical microscope. Moreover, the mucosal thickening in each section was measured in terms of diameter. Results: The epithelialization rate was significantly higher in the AE group than in the control group. Mucosal thickening was not significantly different between the groups. Conclusions: Transplanting amniotic epithelial cells into the ulcer promoted ulcer epithelialization. Amniotic epithelial cell transplantation is a potential method for the management of ulcer scar stenosis following esophageal endoscopic submucosal dissection.